THE INFLUENCE OF DEFERRED TAX EXPENSE, CAPITAL INTENSITY, LEVERAGE, AND CORPORATE SOCIAL RESPONSIBILITY ON TAX AGGRESSIVENESS - Dzihni Ariza; Zirman Zirman; Devi Safitri (Universitas Tidar, 2024)
The objective of this research is to determine how tax aggressiveness is affected by factors like as leverage, deferred tax cost, capital intensity, and corporate social responsibility (CSR). The sample group for this study consists of manufacturing businesses that will be trading on the Indonesia Stock Exchange (IDX) between 2019 and 2021. The 78 firms that made up the sample were researched over a period of three years using secondary data derived from financial and annual reports as well as purposeful sampling approaches. Multiple linear regression is the method used for analysis. According to the findings, tax aggressiveness is negatively affected by capital intensity and CSR. Leverage has a positive effect on tax aggressiveness. Then, deferred tax expense has no effect on tax aggressiveness.